Analisis Pembelajaran Bahasa Indonesia dalam Kurikulum 2013 dan Kurikulum Merdeka di Sekolah Dasar - Liana Liana; Adi Putra Suramana Gurusinga; Putri Dwi Grace Cecilia Damanik; Shinta Pratiwi Cibro; Indra Yeremia Lubis; Rodo Amantuah Sitanggang; Marta Angelina S. Telaumbanua (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to analyze and compare Indonesian language learning in the 2013 Curriculum and the Merdeka Curriculum at the elementary school level. The research employed a library research method with a qualitative descriptive approach. The data sources consisted of official government documents, the Regulation of the Minister of Education and Culture Number 37 of 2018 concerning Core Competencies and Basic Competencies, the Merdeka Curriculum Learning Outcomes document, as well as relevant books and scientific journal articles. Data were collected through documentation studies of various literature sources. The focus of the study included the comparison of learning objectives, curriculum structure, learning approaches, the roles of teachers and students, and assessment systems in both curricula. The data were analyzed using descriptive comparative analysis through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that the 2013 Curriculum implements text-based learning with a structure of Core Competencies and Basic Competencies organized by grade and semester, whereas the Merdeka Curriculum adopts phase-based Learning Outcomes that are more flexible, student-centered, and provide teachers with greater autonomy in designing instruction and implementing project-based learning. In conclusion, although the two curricula differ in curriculum structure, learning approaches, and assessment systems, they share the same goal of developing students’ Indonesian language competencies effectively in accordance with learners’ needs and contemporary educational demands.